Metabolic and Transcriptional Profiles of Dunaliella viridis Supplemented With Ammonium Derived From Glutamine - Dums, Jacob; Murphree, Colin; Vasani, Naresh; Young, Danielle; Sederoff, Heike (Frontiers in Marine Science, 2018)
Algal biofuel production requires an input of synthetic nitrogen fertilizer. Fertilizer synthesized via the Haber-Bosch process produces CO2 as a waste byproduct and represents a substantial financial and energy investment. Reliance on synthetic fertilizer attenuates the environmental significance and economic viability of algae production systems. To lower fertilizer input, the waste streams of algal production systems can be recycled to provide alternative sources of nitrogen such as amino acids to the algae. The halophytic green alga Dunaliella viridis can use ammonium (NH4+) derived from the abiotic degradation of amino acids, and previously, supplementation of NH4+ from glutamine degradation was shown to support acceptable levels of growth and increased neutral lipid production compared to nitrate. To understand the effect of glutamine-released NH4+ on algae growth and physiology, metabolite levels, growth parameters, and transcript profiles of D. viridis cultures were observed in a time course after transition from media containing nitrate as a sole N source to medium containing glutamine, glutamate, or a N-depleted medium. Growth parameters were similar between glutamine (NH4+) and nitrate supplemented cultures, however, metabolite data showed that the glutamine supplemented cultures (NH4+) more closely resembled cultures under nitrogen starvation (N-depleted and glutamate supplementation). Neutral lipid accumulation was the same in nitrate and glutamine-derived NH4+ cultures. However, glutamine-derived NH4+ caused a transcriptional response in the immediate hours after inoculation of the culture. The strong initial response of cultures to NH4+ changed over the course of days to closely resemble that of nitrogen starvation. These observations suggest that release of NH4+ from glutamine was sufficient to maintain growth, but not high enough to trigger a cell transition to a nitrogen replete state. Comparative transcript profiling of the nitrogen-starved and nitrate-supplied cultures show an overall downregulation of fatty acid synthesis and a shift to starch synthesis and accumulation. The results indicate that a continuous, amino acid derived slow release of NH4+ to algae cultures could reduce the amount of synthetic nitrogen needed for growth, but optimization is needed to balance nitrogen starvation and cell division.